(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
In the article the problem of philosophical views Valerian Pidmohylny. Attention to undertake analytical work on the impact of Ukrainian literature Ukrainian, European (especially French) and Russian views on the formation of ideology V. Pidmohylny. The analysis involved a translation artistic practice and writer.